2011
DOI: 10.1007/s11250-011-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Egg production and quality under three housing systems in the tropics

Abstract: The aim of this study was to evaluate egg production and quality of Rhode Island Red (RIR) laying hens in an outdoor system in the subhumid tropic. Eighty RIR laying hens were measured in two periods and housed randomly under three treatments: outdoor (O), indoor (I) and in conventional cages (C). Egg weight (55.88, 53.76 and 57.16 g, for O, I and C, respectively), food intake/hen/day (138.94, 129.74 and 162.90 g, for O, I and C, respectively) and food efficiency (3.13, 3.22 and 3.96 for O, I and C, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
(24 reference statements)
3
3
0
1
Order By: Relevance
“…As can be seen from this finding, contrary to the expectations of the consumers' organic and free-range eggs yolk color, eggs obtained from these systems had lighter yolks, but this difference was not statistically significant (p>0.05) ( Table 1). Parallel to our results, some studies on this subject reported that there was no significant difference in the yolk color due to rearing systems 10,19 , while some other studies reported vise versa 1,9,11,16,17 . There was no significant difference between groups on analysis of the effect of shell color on yolk color (p>0.05) ( Table 2).…”
supporting
confidence: 87%
See 3 more Smart Citations
“…As can be seen from this finding, contrary to the expectations of the consumers' organic and free-range eggs yolk color, eggs obtained from these systems had lighter yolks, but this difference was not statistically significant (p>0.05) ( Table 1). Parallel to our results, some studies on this subject reported that there was no significant difference in the yolk color due to rearing systems 10,19 , while some other studies reported vise versa 1,9,11,16,17 . There was no significant difference between groups on analysis of the effect of shell color on yolk color (p>0.05) ( Table 2).…”
supporting
confidence: 87%
“…In this study, the heaviest eggs were cage, then freerange and organic. Similarly, results were reported indicating free-range eggs lighter than cage eggs 1,17 . In our country, the weight range for M (Medium) size grade A table eggs in TFCEN was indicated as 53-63 g 13 .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Conversely, Wang et al (2009) found no difference in the average albumen height and Haugh unit values from conventional cage and outdoor production systems. Additionally, Varguez-Montero et al (2012) found no differences in albumen height and Haugh unit when comparing conventional cage, outdoor, and indoor production systems and Hidalgo et al (2008) found similar Haugh unit values in Italian retail eggs from free range, cage, and barn production. Whereas the overall albumen height and Haugh unit values were found to be different between conventional and enriched colony cage production in the current study, the rate of decline at 4, 6, and 12 wk of storage for the 2 parameters was never significantly different between any of the housing systems.…”
Section: Resultsmentioning
confidence: 77%